2017
DOI: 10.3390/ijerph14101121
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Concentration in Maternal and Umbilical Cord Blood by Season

Abstract: Summer is generally considered to be the season when the body is well-supplied with vitamin D. The aim of this study was to compare maternal and umbilical cord blood concentrations of vitamin D during two extreme seasons of the year in Poland—winter and summer. A total of 100 pregnant women with no history of chronic diseases before pregnancy were included in the study. Pre-delivery maternal venous blood and neonatal cord blood samples were collected and total 25(OH)D concentration was measured. Data on vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…The placenta is formed at gestational week 4 allowing nutrients to reach the developing fetus. From this time until delivery 25(OH)D 3 easily crosses the placenta reaching concentrations in fetal cord blood equivalent to 87% of the maternal blood levels (164). The biological active vitamin D does not cross the placenta (Figure 3).…”
Section: Maternal Vitamin D Deficiency Association With Fetal Origin mentioning
confidence: 99%
“…The placenta is formed at gestational week 4 allowing nutrients to reach the developing fetus. From this time until delivery 25(OH)D 3 easily crosses the placenta reaching concentrations in fetal cord blood equivalent to 87% of the maternal blood levels (164). The biological active vitamin D does not cross the placenta (Figure 3).…”
Section: Maternal Vitamin D Deficiency Association With Fetal Origin mentioning
confidence: 99%
“…Hypovitaminosis D is more likely to take place during winter months because of the ineffectiveness of the winter sun to facilitate vitD synthesis [7]. Similar patterns were reported in studies from other countries [8][9][10][11][12]. In winter, sunlight travels longer through the atmosphere where the UVB is absorbed to a greater degree.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, Naseh et al [36] and Kilicaslan et al [37] detected VD deficiency rates of 27% and 53% and insufficiency rates of 73% and 47%, respectively, in their series of pregnant women. Moreover, Wierzejska et al [38] detected higher VD levels in maternal and umbilical cord blood in summer than in winter, but only 16% of studied pregnant women had the optimal VD level during summer. Recently, in 2018; Gustafsson et al [39] reported decreased 1,25(OH)2D in 45% of pregnant women with significant difference than women with adequate vitamin D status and found no association of VD indices and parathyroid hormone changes during pregnancy.…”
Section: Discussionmentioning
confidence: 95%